Framing the South : Hollywood, television, and race during the Civil Rights struggle - Graham, Allison (Johns Hopkins University Press, 2001)
"What patterns emerge in media coverage and character depiction of southern men and women, black and white, in the years between 1954 and 1976? How do portrayals of the region and the equal rights movement illuminate the spirit and experience of the South - and of the nation as a whole? In Framing the South, Allison Graham examines the ways in which the media, particularly television and film, presented southerners during the period of the civil rights revolution."--Jacket